Two gods in heaven: Jewish concepts of God in antiquity - Schäfer, Peter (Princeton University Press, 2020)
Cover -- Title Page -- Copyright Page -- CONTENTS -- Introduction: One God? -- PART I. SECOND TEMPLE JUDAISM -- 1 The Son of Man in the Vision of Daniel -- 2 The Personified Wisdom in the Wisdom Literature -- 3 The Divinized Human in the Self-Glorification Hymn from Qumran -- 4 The Son of God and Son of the Most High in the Daniel Apocryphon from Qumran -- 5 The Son of Man-Enochin the Similitudes of the Ethiopic Book of Enoch -- 6 The Son of Man-Messiah in the Fourth Book of Ezra -- 7 The Firstborn in the Prayer of Joseph -- 8 The Logos according to Philo of Alexandria -- Transition: From Pre-Christian to Post-Christian Judaism -- PART II: RABBINIC JUDAISM AND EARLY JEWISH MYSTICISM -- 9 The Son of Man in the Midrash -- 10 The Son of Man-Messiah David -- 11 From the Human Enoch to the Lesser God Metatron -- Conclusion: Two Gods -- Abbreviations -- Notes -- Bibliography -- Index.